Grammar of the shot - Bowen, Christopher J. (Routledge, 2018)
The newly-revised and updated fourth edition of Grammar of the Shot teaches readers the principles behind successful visual communication in motion media through shot composition, screen direction, depth cues, lighting, camera movement, and shooting for editing. Many general practices are suggested that should help to create rich, multi-layered visuals. Designed as an easy-to-use reference, Grammar of the Shot presents each topic succinctly with clear photographs and diagrams illustrating key concepts, practical exercises, and quiz questions, and is a staple of any filmmaker's library. New to the fourth edition: an expanded companion website at www.routledge.com/cw/Bowen, offering downloadable scenes and editable raw footage so that students can practice the techniques described in the book, and instructional videos showcasing examples of different compositional choices; new and expanded quiz questions and practical exercises at the end of each chapter to help test readers on their knowledge using real-world scenarios; updated topic discussions, explanations, illustrations, and visual examples. Together with its companion volume, Grammar of the Edit , the core concepts discussed in these books offer concise and practical resources for both experienced and aspiring filmmakers.